2011
DOI: 10.1200/jco.2011.35.3714
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Recurrence and Chemotherapy Benefit for Patients With Node-Negative, Estrogen Receptor–Positive Breast Cancer: Recurrence Score Alone and Integrated With Pathologic and Clinical Factors

Abstract: RSPC refines the assessment of distant recurrence risk and reduces the number of patients classified as intermediate risk. Adding clinicopathologic measures did not seem to enhance the value of RS alone nor the individual biology RS identifies in predicting chemotherapy benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 15 publications
1
104
1
Order By: Relevance
“…Incorporating clinical data (tumour stage, grade and age) for patients with node-negative disease into the test improves its performance as a prognostic test but crucially does not improve its ability to predict chemotherapy sensitivity. 64,70 A number of studies (e.g. Ademuyiwa et al 71 and Albanell et al 72 ), including two conducted within the UK, 73,74 have shown that the use of Oncotype DX leads to changes in chemotherapy decisions in about one-third of patients, although these studies involve small sample sizes and often have poorly described protocols.…”
Section: Individual Multiparameter Assaysmentioning
confidence: 99%
“…Incorporating clinical data (tumour stage, grade and age) for patients with node-negative disease into the test improves its performance as a prognostic test but crucially does not improve its ability to predict chemotherapy sensitivity. 64,70 A number of studies (e.g. Ademuyiwa et al 71 and Albanell et al 72 ), including two conducted within the UK, 73,74 have shown that the use of Oncotype DX leads to changes in chemotherapy decisions in about one-third of patients, although these studies involve small sample sizes and often have poorly described protocols.…”
Section: Individual Multiparameter Assaysmentioning
confidence: 99%
“…23,[26][27][28]31 In a meta-analysis of combined data sets from the NSABP and TransATAC trials, a prognostic score that combined RS with selected clinicopathological features provided improved risk assessment over RS alone (P < 0.001) and classified fewer patients as intermediate risk. 32 • A recent meta-analysis of four studies using a fixedeffects model found a hazard ratio of 2.97 (95% CI 2.19-4.0) for a high RS versus an intermediate or low RS. However, this analysis combined studies on nodenegative and node-positive patients and included one study in which the outcome was locoregional rather than distant recurrence.…”
Section: Clinical Validitymentioning
confidence: 99%
“…(Table 3) 31 or a score that combined RS with selected clinicopathological factors. 32 • When evaluated by the GRADE criteria, the quality of evidence indicating that Oncotype DX RS has clinical utility was assessed as very low. 21 Low quality was not due to conflicting studies or studies demonstrating lack of benefit.…”
Section: Clinical Utilitymentioning
confidence: 99%
“…This test has been shown to have predictive value in identifying women with either node-positive or node-negative breast cancer who are unlikely to respond to adjuvant chemotherapy and so may choose to forgo adjuvant chemotherapy. 30,31 This test is eligible for review with our tool, is based on its ability to predict drug response (as well as recurrence risk), and proceeds through clinical review to economic review. OncotypeDx has potentially large budget impact, reasonable prevalence (greater than 20% of women have actionable results), and a relatively high price for a test.…”
Section: Q10mentioning
confidence: 99%